A qualitative study of nurses' perspective about the impact of end‐of‐life communication on the goal of end‐of‐life care in nursing home. Issue 2 (28th April 2020) - Gonella, Silvia; Basso, Ines; Clari, Marco; Dimonte, Valerio; Di Giulio, Paola
Abstract : Background: With a growing nursing home population suffering from chronic progressive illnesses and evolving patterns of comorbidities, end‐of‐life communication takes on a critical role to enable healthcare professionals to gather information about the resident's wishes for care at the end‐of‐life and organise the care plan accordingly. Aim: To explore nurses' perspective about the process by which end‐of‐life communication impacts on the goal of end‐of‐life care in nursing home residents. Design: A qualitative descriptive research design based on thematic analysis was performed. Fourteen nurses involved in the care of residents during their last week of life were recruited across 13 Italian nursing homes and accounted for 34 semi‐structured interviews. A combined approach of analysis that incorporated a data‐driven inductive approach and a theory‐driven one was adopted. Results: Twelve themes described how end‐of‐life communication may contribute to adjust the care plan in nursing home according to the nurses' perspective. Five antecedents (i.e. life crisis or transitions, patient‐centered environment, arising the question of possible dying, quality of relationships and culture of care) influenced the establishment and quality of communication, and five attributes depicted the characteristics and potential mechanisms of end‐of‐life communication (i.e. healthcare professional‐resident and healthcare professional‐family carers communication, knowledge of family carers' preferences, knowledge of residents' preferences, family carers and residents understanding, and shared decision‐making), while curative‐oriented and palliative‐oriented care goals emerged as consequences. Conclusion: This study provides insight into the nursing perspective of end‐of‐life communication between healthcare professionals and bereaved family carers of nursing home residents. Several factors influenced the occurrence and quality of end‐of‐life communication, which contributed to the transition towards palliative‐oriented care by using and improving knowledge about family cares' and resident's preferences for end‐of‐life care, promoting family carers and residents understanding about prognosis and treatments available, and fostering shared decision‐making.